2018
DOI: 10.1029/2017tc004916
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Structure and Quaternary Acceleration of Deformation Rates in Central Washington Revealed by Stream Profile Inversion, Potential Field Geophysics, and Structural Geology of the Yakima Folds

Abstract: Abtract Post-Miocene tectonic uplift along fault-cored anticlines within central Washington produced the Yakima Fold Province, a region of active NNE-SSW shortening in the Cascadian backarc. The relative timing and rate of deformation along individual structures is coarsely defined yet imperative for seismic hazard assessment. In this work, we use geomorphic and geophysical mapping, stream profile inversion, and balanced cross-section methods to constrain fault geometries and slip rates in the Yakima Canyon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…This is seen in the relative motion across the NFZ discussed here, but the consequences of this difference in plate motion have also been invoked to explain deformational behavior of the overriding NAM. Staisch et al () invoke the separation of the EXP and JdF plate as a mechanism to change convergence rates and orientations (with respect to the overriding NAM), leading to an increase in deformation rates in the Yakima Fold province at approximately 4–2 Ma. Both Staisch et al () and Mullen et al () further imply that this separation between the EXP and JdF plate must be a throughgoing plate boundary structure, perhaps even leading to the development of a slab window beneath Vancouver Island south of the onshore extension of the NFZ.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…This is seen in the relative motion across the NFZ discussed here, but the consequences of this difference in plate motion have also been invoked to explain deformational behavior of the overriding NAM. Staisch et al () invoke the separation of the EXP and JdF plate as a mechanism to change convergence rates and orientations (with respect to the overriding NAM), leading to an increase in deformation rates in the Yakima Fold province at approximately 4–2 Ma. Both Staisch et al () and Mullen et al () further imply that this separation between the EXP and JdF plate must be a throughgoing plate boundary structure, perhaps even leading to the development of a slab window beneath Vancouver Island south of the onshore extension of the NFZ.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…However, the bedrock erodibility, k, value of 0.10 ± 0.04 m (1−2m) Myr -1 is relatively small, even if compared to equivalent measures derived from analysis of other basaltic landscapes (e.g. Staisch et al, 2018;Stucky de Quay et al, 2019). A small k value implies a long landscape response time, which is the ability to retain tectonic or climate signals in topography.…”
Section: Comparison Of Erosional Parameters To Existing Workmentioning
confidence: 88%
“…Boulton and Whittaker, 2009;Pavano et al, 2016), revealed changes in fault slip rates (e.g. Commins et al, 2005;Whittaker et al, 2008;Whittaker and Walker, 2015;Kent et al, 2017;Staisch et al, 2018), estimated the temporal evolution of dynamic topography (e.g. Roberts and White, 2010;Miller et al, 2012;Roberts et al, 2012), and modelled vertical motions of large continental regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compressional structures east of the High Cascades have been tracked westward into the arc, suggesting that this segment of the Cascade arc was constructed on crust that was being shortened after circa 17 Ma (Beeson & Tolan, 1990; Blakely et al, 2011; Brocher et al, 2017; Hammond, 1979). The southernmost cooling ages from Reiners et al (2002, 2003) are situated at the same latitude as the northern Yakima Fold Belt and are younger than circa 17 Ma (Figure 10) (Blakely et al, 2011; Kelsey et al, 2017; Staisch et al, 2017, 2018). Because the Yakima Fold Belt structures and shortening are restricted to this segment of the Cascades, the Yakima Fold Belt may contribute to rock uplift in only southern Washington or northern Oregon, but not along the entire Cascade Range.…”
Section: Discussionmentioning
confidence: 99%